2020
DOI: 10.1353/asi.2020.0020
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Ritual Funerary Activity of the Late Prehistoric Southern Kanas Region (Xinjiang, China)

Abstract: Identifying peaks in anthropogenic activity in a landscape is an important starting point for understanding past social dynamics in the longue durée. Through intensive surveys and remote sensing surveys of the Heiliutan Basin (Heiliutan Dacaoyuan 黑流滩大草原) in the southern Kanas Region (Kanasi 喀纳斯), Xinjiang, China, a high-resolution dataset for over 4000 years of material culture is established. The complete coverage of the area of interest allows for the quantification of ritual funerary activity based on the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…This strategic positioning likely added symbolic meaning to the structure, perhaps even serving as a social marker recognizable by nomadic pastoral groups from afar. This is in line with previous archeological and geomorphological research across Xinjiang, which has shown that during the Bronze and Iron Ages, special buildings devoted to collective ceremonies and rituals were strategi-cally placed in locations like mountain peaks, open valleys, and occasionally alluvial fans, chosen for their ecological, climatic, environmental, and socio-political and symbolic significance [112][113][114]. Centripetal structures, which have been identified across the Eastern Tianshan region, were located in similar settings.…”
Section: Centripetal Compound Buildings In the Eastern Tianshan Mount...supporting
confidence: 87%
“…This strategic positioning likely added symbolic meaning to the structure, perhaps even serving as a social marker recognizable by nomadic pastoral groups from afar. This is in line with previous archeological and geomorphological research across Xinjiang, which has shown that during the Bronze and Iron Ages, special buildings devoted to collective ceremonies and rituals were strategi-cally placed in locations like mountain peaks, open valleys, and occasionally alluvial fans, chosen for their ecological, climatic, environmental, and socio-political and symbolic significance [112][113][114]. Centripetal structures, which have been identified across the Eastern Tianshan region, were located in similar settings.…”
Section: Centripetal Compound Buildings In the Eastern Tianshan Mount...supporting
confidence: 87%
“…Ongoing dendrochronological studies will clarify the relationship. The current evidence points to the construction of both monuments within one or two generations (Zaitseva et al 2007;Caspari et al 2020a). Monumental architecture is novel in the narrow geographic frame of the Uyuk Valley in the Early Iron Age.…”
Section: Proximity As Familiaritymentioning
confidence: 72%
“…3). Radiocarbon dates, later in combination with wiggle matching, situated the burial mound in the 9th century BCE (Caspari et al 2020a). Further geophysical and remote sensing research clarified the peripheral context of the monument, revealing a large number of stone circles around the main mound (Fig.…”
Section: Proximity As Familiaritymentioning
confidence: 98%
See 1 more Smart Citation
“…Bronze Age stone-based habitation sites might be far more widespread than previously assumed. This type of monument extends into northern Xinjiang [23,24], Kazakhstan [25], the Russian Altai and Tuva Republic, although there is an ongoing debate whether smaller versions are connected to seasonal habitation [26] or should rather be interpreted within a ritualistic framework [27,28]. Archaeologically, investment in construction of stone houses is often taken to indicate permanent settlement, but this is clearly not the case in the Bortala Valley.…”
Section: Plos Onementioning
confidence: 99%